US policy spillover(?): China's accession to the WTO and rising exports to the EU - Karsten Mau (Leuphana Universität Lüneburg, Institut für Volkswirtschaftslehre, 2015)
The paper offers a novel explanation for China's manufacturing exports performance after WTO entry. Building on stylized facts about low-wage country exporters, a theoretical model is developed to analyze reduced trade policy uncertainty. A global (non-destination specific) component of exporting fixed costs facilitates transmission of bilateral policy changes to multilateral export performance. The empirical analysis exploits the removal of US tariff uncertainty in conjunction with China's WTO accession, and examines its effect on China's exports to the EU. The results reveal that: (i) the structure of China's export boom to the EU conforms to the pattern of US tariff uncertainty; (ii) the adjustment takes place at the extensive margin; and (iii) the effect phases out after a few years. These findings have implications for the scope of international policy negotiations and provide suggestive evidence on the nature of fixed costs manufacturing firms in low-wage countries must overcome.
Keywords: F13; F14; D84; O24; 330; Exports; China; WTO; Policy Uncertainty; Fixed Costs; Spillover